On-farm demonstration of improved field pea varieties in selected districts of bale highlands, Oromiya national regional state, Ethiopia (International Journal of Agricultural Research, Innovation and Technology, 2022)
On-farm demonstration of improved field pea varieties was conducted in Goba, Sinana and Agarfa districts of Bale zone. The main objective of the study was to demonstrate and evaluate recently released Hortu variety along with standard check. The demonstration was under taken on single plot of 10m x 10m area for each variety with row planting, recommended seed rate of 75 kg ha-1 and fertilizer rate of 100 kg ha-1 NPS. Mini-field day involving different stakeholders was organized at each respective site. Yield data per plot was recorded and analysed using descriptive statistics, while farmers’ preference to the demonstrated varieties was identified using focused group discussion and summarized using pair wise ranking methods. The demonstration result revealed that Hortu variety performed better than the standard check Harena variety with an average yield of 36.30 qt ha-1 and 31.42 qt ha-1, respectively. Hortu variety had 15.53% yield advantage over the standard check. Furthermore, farmers selected this variety. Thus, Hortu variety was recommended for further scaling up.Int. J. Agril. Res. Innov. Tech. 12(1): 4-7, June 2022